2018
DOI: 10.1097/lbr.0000000000000504
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional (3D) Printed Model to Plan the Endoscopic Treatment of Upper Airway Stenosis

Abstract: Our 3D airway model in the management of airway stenosis is useful for procedural planning, rehearsal, and education. The fidelity level of the 3D model remains the main concern for its wider use in patient care. Thus, our impressions should be confirmed by future prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Eight studies used 3D-printed models for preoperative planning and simulation of airway management in complex cases, five of which were in children. 1724 Kavanagh and colleagues developed four models using 3D printing, including three direct-printed models made with different materials, including polylactic acid (PLA), acrylonitrile butadiene styrene and high-impact polystyrene, and a silicone model made from a 3D-printed cast. 18 These were tested by four otolaryngologists who concluded that the cast model was significantly better in terms of tissue characteristics, ease of tissue manipulation and overall accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies used 3D-printed models for preoperative planning and simulation of airway management in complex cases, five of which were in children. 1724 Kavanagh and colleagues developed four models using 3D printing, including three direct-printed models made with different materials, including polylactic acid (PLA), acrylonitrile butadiene styrene and high-impact polystyrene, and a silicone model made from a 3D-printed cast. 18 These were tested by four otolaryngologists who concluded that the cast model was significantly better in terms of tissue characteristics, ease of tissue manipulation and overall accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…21 Three other studies included printed models to plan and rehearse intubation preoperatively in complex cases related to a laryngectomy, tracheal stenosis and a head and neck cancer. 2224…”
Section: Resultsmentioning
confidence: 99%
“…The distance between the proximal end of the stenosis and vocal cord could be precisely shown by the 3D model, which could facilitate clinical decision making for each patient. Furthermore, the 3D model could also be used for resident teaching and patient education ( 10 , 15 ). However, it should be noted that the major limitation of customized stents is the time required to manufacture the stent.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) printing is being employed in a variety of surgical specialties to improve patient care and is becoming standard of care in some [1]. These models enable preoperative in vitro planning [2,3], production of tailor-made grafts and stents [4,5], advanced training of surgical residents and improved patient education [6]. In otolaryngology, recent studies reported the use of 3D models of the larynx and trachea for laryngotracheal reconstruction (LTR) rehearsal [7], for training in endoscopic balloon dilations of subglottic stenosis [8], for creating tissue-engineered airway grafts [9,10], and for other procedures [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%